2005
DOI: 10.1097/01.mop.0000172819.72013.5d
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplement use in adolescents

Abstract: As the dietary supplement industry is now a multi-billion dollar industry, there is growing pressure, and a subsequent need for research to establish the efficacy and safety of these products particularly for adolescent users. The psychological and educational components of such use cannot be ignored as they play an equally important role in the health and safety of adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 26 publications
3
28
0
Order By: Relevance
“…To date, three deaths in college and professional sports have been attributed, at least in part, to ephedra (Keisler & Hosey, 2005), including the death of a U.S. Major League Baseball pitcher in 2003 (Mihoces, 2003). Adolescent athletes use ephedrine as a quick way to increase athletic ability and decrease body fat (Dorsch & Bell, 2005) and are the least concerned with safety and health issues. Bents and Marsh found that 49% of the athletes in an American college hockey conference had used ephedra at least once to improve performance, and 20% had used pseudoephedrine in the last 30 days.…”
Section: Guaranamentioning
confidence: 99%
“…To date, three deaths in college and professional sports have been attributed, at least in part, to ephedra (Keisler & Hosey, 2005), including the death of a U.S. Major League Baseball pitcher in 2003 (Mihoces, 2003). Adolescent athletes use ephedrine as a quick way to increase athletic ability and decrease body fat (Dorsch & Bell, 2005) and are the least concerned with safety and health issues. Bents and Marsh found that 49% of the athletes in an American college hockey conference had used ephedra at least once to improve performance, and 20% had used pseudoephedrine in the last 30 days.…”
Section: Guaranamentioning
confidence: 99%
“…Also, guidelines for conducting in vitro and in vivo studies and their relevance for clinical safety data are defined. Apparently, these initiatives are necessary since efficacy and safety of dietary supplements and herbals is poorly documented, and the awareness of consumers and health professionals towards nutritional supplements as a potential source of health damage is low [4,47].…”
Section: Productmentioning
confidence: 99%
“…Consumers turn to such products for presumed benefits regarding enhanced physical performance during sports activities, disease prophylaxis, improvement of nutritional status, and, particularly, weight reduction [2][3][4]. Consequently, dietary weight loss products have become a multi-billion market [5], and although not recommended for losing weight by nutrition expert panels [6,7], their long-term use without medical consultation is frequent [8].…”
Section: Introductionmentioning
confidence: 99%
“…Nutritional supplements are typically used for their actual or anecdotal physiological effects in increasing performance and endurance, health maintenance or preventing injuries [13-16], and the extent and amount of ergogenic 'drugs' and supplements used by athletes shows a growing trend [17]. Research linking supplement use to involvement in physical activity and previous studies on decision making patterns among these groups has focused on user subgroup classifications [18-23]. While this enables an understanding of the gross difference in the patterns of use between groups of users, it fails to give an explanation for why those differences might occur.…”
Section: Supplement Use In Sportmentioning
confidence: 99%